Case report: Two novel intergenic region-ALK fusions in non-small-cell lung cancer resistant to alectinib: A report of two cases - Liao, Shan; Sun, Huiying; Wu, Jianhua; Lu, Hao; Fang, Yisheng; Wang, Yuanyuan; Liao, Wangjun (Frontiers in Oncology, 2022)
Background: The anaplastic lymphoma kinase (ALK) mutation, also known as the diamond mutation in non–small-cell lung cancer (NSCLC), has been treated with tremendous success since it was first reported in 2007. Alectinib, a second generation ALK-Tyrosine kinase inhibitor (TKI), has been reported to have significantly longer progression- free survival (PFS) than first generation ALK inhibitors in untreated ALK positive NSCLC. However, the clinical efficacy of ALK-TKIs on rare ALK fusions remains unclear. In recent years, with the popularity of next-generation sequencing (NGS) technology, an increasing number of novel ALK fusion partners have been reported, but the responses are heterogeneous among different ALK fusions. Considering the inconsistent reactions, the clinical efficacy of ALK-TKIs in rare ALK gene fusions remains to be evaluated in more cases. Methods: To seek for individualized therapy, the tumor tissues acquired during biopsy were sent for genomic testing by NGS based on a 139-gene panel and a 425-gene panel in a centralized clinical testing center (GENESEEQ Technology Inc, Nanjing, China). See supplementary Material 1 for more details about the methods for DNA-based NGS, RNA-based NGS. Results: We present two cases of patients with lung adenocarcinoma harboring two novel Intergenic Region (IGR)-ALK rearrangements detected by DNA sequencing, which had limited clinical response to ALK-TKIs but showed sensitivity to chemotherapy combined with bevacizumab therapy in patient 2, with a PFS of over 1 year up till the last follow‐up assessment. Conclusions: In summary, our cases emphasize the need for comprehensive molecular analysis of different ALK fusion partners at the DNA level to formulate accurate treatment strategies and provide a certain therapeutic reference for these two types of novel IGR-ALK fusions.